2015
DOI: 10.1371/journal.pone.0140615
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Promising Mutants Associated with Egg Production Traits Revealed by Genome-Wide Association Study

Abstract: Egg number (EN), egg laying rate (LR) and age at first egg (AFE) are important production traits related to egg production in poultry industry. To better understand the knowledge of genetic architecture of dynamic EN during the whole laying cycle and provide the precise positions of associated variants for EN, LR and AFE, laying records from 21 to 72 weeks of age were collected individually for 1,534 F2 hens produced by reciprocal crosses between White Leghorn and Dongxiang Blue-shelled chicken, and their geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 54 publications
3
50
1
Order By: Relevance
“…In our previous GWAS studies [37, 38, 39], 37 genes played a key role in egg production and feed efficiency in chicken such as egg weight (EW), egg number (EN), feed intake (FI), feed conversion ratio (FCR) and residual feed intake(RFI). Twenty-two genes overlapped with core regions had been demonstrated to be associated with economic traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous GWAS studies [37, 38, 39], 37 genes played a key role in egg production and feed efficiency in chicken such as egg weight (EW), egg number (EN), feed intake (FI), feed conversion ratio (FCR) and residual feed intake(RFI). Twenty-two genes overlapped with core regions had been demonstrated to be associated with economic traits.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two genes overlapped with core regions had been demonstrated to be associated with economic traits. For instance, the NCAPG gene locating on chromosome 4 had been identified influencing both egg weight and body weight simultaneously in a pleiotropic manner [37]; the CLSPN gene on chromosome 23 displayed significant haplotype [38], may related with egg number via affecting the function of ovary and uterus[40,41]. These results could effectively elucidate that some important economic traits like egg production had undergone selection.…”
Section: Discussionmentioning
confidence: 99%
“…PPARGC1A may affect egg weight by regulating energy and cholesterol metabolism. Yuan et al (2015) detected nine genome-wide loci that significantly affected egg number during the laying phases of 21-26, 27-36, and 37-72 weeks using GWAS technology. Liao et al (2016) found a genome-wide significant locus (ss1985401199) located on the sex chromosome Z, which was associated with egg number in hens at 25-45 weeks.…”
Section: Egg Numbermentioning
confidence: 99%
“…To characterize the genetic variations and genetic relationships among different populations using DNA markers, a total of 28 identified SNP markers, including 14 growth or carcass traits associated loci and 14 egg laying related genome positions, were selected from the previous reports [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. By using the MassArray technology, an Agena Bioscience MassARRAY System which is capable of efficiently genotyping tens to hundreds of SNPs with high accuracy, we detected the genotype frequency distributions of the 28 SNP markers in seven populations including four lowly selected as well as one moderately selected Sichuan native chicken populations, one commercial broiler line and one commercial layer line [34,35].…”
Section: Introductionmentioning
confidence: 99%